Polymer compositions for laser direct structuring
By using polymer compositions of high naphthalene thermochromic liquid crystal polymers and laser-activated additives, the deficiencies in the dielectric constant and mechanical properties of existing materials in the laser direct molding process are solved, and the effects of low dielectric constant and low dissipation factors are achieved for 5G applications.
Patent Information
- Application Number
- CN202080078291.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-27
- Filing Date
- 2020-08-19
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2040-08-19
AI Technical Summary
It is difficult for existing materials to achieve low dielectric constant and good mechanical properties in laser direct molding processes, especially in high-frequency applications, where power consumption and heat generation problems are increased.
Using a polymer composition containing a high naphthalene thermogenic liquid crystal polymer and a laser-activated additive, the dielectric constant and mechanical properties of the material are optimized by adjusting the repeating unit content in the liquid crystal polymer and the proportion of additives.
It realizes low dielectric constant and low dissipation factor over a wide frequency range, suitable for 5G applications, while providing excellent thermal, mechanical and processability.
Smart Images

Figure CN114729177B_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of U.S. Provisional Patent Application Serial No. 62 / 898,188, filed September 10, 2019; U.S. Provisional Patent Application Serial No. 62 / 925,274, filed October 24, 2019; U.S. Provisional Patent Application Serial No. 62 / 951,039, filed December 20, 2019; U.S. Provisional Patent Application Serial No. 62 / 972,195, filed February 10, 2020 application; U.S. Provisional Patent Application Serial Number 62 / 994,329, filed on March 25, 2020; U.S. Provisional Application Serial Number 63 / 009,017, filed on April 13, 2020; U.S. Provisional Application Serial Number 63 / 024,584, filed on May 14, 2020; and U.S. Provisional Application Serial Number 63 / 056,865, filed on July 27, 2020, the entire contents of which are incorporated herein by reference in their entirety. Background Art
[0003] In order to form antenna structures of various electronic components, molded interconnect devices (Molded interconnect device, MID) generally include a plastic substrate on which conductive elements or paths are formed. Such MID devices are therefore three-dimensional molded parts with integrated printed conductors or circuit layouts. It is becoming increasingly popular to form MIDs using a laser direct structuring (LDS) process, in which a computer-controlled laser beam travels on a plastic substrate to activate its surface at the location where the conductive path is to be located. Using a laser direct structuring process, conductive element widths and spacings of 150 microns or less can be obtained. Therefore, the MID formed by this process saves space and weight in the final application. Various materials have been proposed to form a plastic substrate for laser direct structuring MID devices. For example, one such material is a blend of polycarbonate, acrylonitrile butadiene styrene (ABS), copper chromium oxide spinel, and bisphenol A diphenyl phosphate (BPADP) flame retardant. However, one problem with such a material is that flame retardants tend to have an adverse effect on the mechanical properties of the composition (e.g., deformation temperature under load), which makes it difficult to use in laser direct structuring processes. Liquid crystal polymer formulations have been developed to try to address these issues, but these formulations tend to have dielectric constants that are too high to make them suitable for high-frequency applications (such as 5G), where power consumption and heat generation increase.
[0004] Therefore, there is a need for polymer compositions that can be activated by laser direct structuring and that have a relatively low dielectric constant. Summary of the invention
[0005] According to one embodiment of the present invention, a polymer composition is disclosed, comprising at least one laser-activatable additive and at least one high naphthalene thermotropic liquid crystal polymer, the high naphthalene thermotropic liquid crystal polymer containing repeating units derived from naphthalene hydroxycarboxylic acid and / or naphthalene dicarboxylic acid in an amount of about 10 mol.% or more. The polymer composition exhibits a dielectric constant of about 5 or less as measured at a frequency of 2 GHz.
[0006] Other features and aspects of the present invention are described in more detail below. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] A full and enabling disclosure of the present invention, including the best embodiment to one skilled in the art, is more particularly set forth in the remainder of the specification, including reference to the accompanying drawings, in which:
[0008] Figures 1 to 2 are front and rear perspective views, respectively, of one embodiment of an electronic assembly in which an antenna system may be employed;
[0009] Figure 3 is a top view of an illustrative inverted-F antenna resonating element for one embodiment of an antenna system;
[0010] Figure 4 is a top view of an illustrative monopole antenna resonating element for one embodiment of an antenna system;
[0011] Figure 5 is a top view of an illustrative slot antenna resonating element for one embodiment of an antenna system;
[0012] Figure 6 is a top view of an illustrative patch antenna resonating element for one embodiment of an antenna system;
[0013] Figure 7 is a top view of an illustrative multi-branch inverted-F antenna resonating element for one embodiment of an antenna system;
[0014] Figure 8 A 5G antenna system including a base station, one or more relay stations, one or more user computing devices, and one or more Wi-Fi repeaters according to aspects of the present disclosure is depicted;
[0015] Fig. 9A shows a top view of an example user computing device including a 5G antenna according to aspects of the present disclosure;
[0016] Fig. 9B A 5G antenna is shown according to aspects of the present disclosure. Fig. 9A A side view of an example user computing device;
[0017] Fig.10 Shows Fig. 9A an enlarged view of a portion of a user computing device;
[0018] Fig.11 shows a side view of a coplanar waveguide antenna array configuration according to aspects of the present disclosure;
[0019] Fig. 12A An antenna array for a massive multiple-input multiple-output configuration according to aspects of the present disclosure is shown;
[0020] Fig. 12B An antenna array formed using laser direct structuring according to aspects of the present disclosure is shown;
[0021] Fig. 12C shows example antenna configurations according to aspects of the present disclosure; and
[0022] Figures 13A to 13C Depicted is a simplified sequential diagram of a laser direct structuring manufacturing process that can be used to form an antenna system. DETAILED DESCRIPTION
[0023] Those skilled in the art will appreciate that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the invention.
[0024] In general, the present invention relates to a polymer composition comprising a combination of a thermotropic liquid crystal polymer and a laser-activatable additive. More specifically, the polymer composition comprises a liquid crystal polymer having a "high naphthalene" content because it contains a relatively high content of repeating units derived from naphthalene hydroxycarboxylic acid and naphthalene dicarboxylic acid (e.g., NDA, HNA) or a combination thereof. That is, the total amount of repeating units derived from naphthalene hydroxycarboxylic acid and / or naphthalene dicarboxylic acid (e.g., NDA, HNA or a combination of HNA and NDA) is typically about 10 mol.% or more of the polymer, in some embodiments about 12 mol.% or more, in some embodiments about 15 mol.% or more, in some embodiments about 18 mol.% or more, in some embodiments about 30 mol.% or more, in some embodiments about 40 mol.% or more, in some embodiments about 45 mol.% or more, in some embodiments about 50 mol.% or more, in some embodiments about 60 mol.% or more, in some embodiments 62 mol.% or more, in some embodiments about 68 mol.% or more, in some embodiments 70 mol.% or more, and in some embodiments about 70 mol.% to about 80 mol.%. Without being limited by theory, it is believed that such "high naphthalene" polymers can reduce the tendency of polymer compositions to absorb water, which can help stabilize the dielectric constant in the high frequency range. That is, such high naphthalene polymers typically have a water absorption of about 0.015% or less, in some embodiments about 0.01% or less, and in some embodiments about 0.0001% to about 0.008% after immersion in water for 24 hours according to ISO 62-1:2008. High naphthalene polymers can also have a moisture absorption of about 0.01% or less, in some embodiments about 0.008% or less, and in some embodiments about 0.0001% to about 0.006% after exposure to a humid atmosphere (50% relative humidity) at a temperature of 23°C according to ISO 62-4:2008.
[0025] By carefully selecting the specific properties and concentrations of the components of the polymer composition, the inventors have found that the resulting composition can exhibit a low dielectric constant over a wide frequency range, making it particularly suitable for 5G applications. That is, as determined by the split post dielectric resonator method at a typical 5G frequency (e.g., 2GHz), the polymer composition can exhibit a low dielectric constant of about 5 or less, about 4.5 or less in some embodiments, about 0.1 to about 4.4 in some embodiments, about 1 to about 4.2 in some embodiments, about 1.5 to about 4 in some embodiments, about 2 to about 3.9 in some embodiments, and about 3.5 to about 3.9 in some embodiments. The dissipation factor (measure of energy loss rate) of the polymer composition can be similarly about 0.05 or less at a typical 5G frequency (e.g., 2GHz), about 0.01 or less in some embodiments, about 0.0001 to about 0.008 in some embodiments, and about 0.0002 to about 0.006 in some embodiments. In fact, in some cases, the dissipation factor can be very low at typical 5G frequencies (e.g., 2 or 10 GHz), such as about 0.003 or less, about 0.002 or less in some embodiments, about 0.001 or less in some embodiments, about 0.0009 or less in some embodiments, about 0.0008 or less in some embodiments, and about 0.0001 to about 0.0007 in some embodiments. Notably, the inventors have also surprisingly found that the dielectric constant and dissipation factor can be maintained within the above ranges even when exposed to various temperatures, such as temperatures from about -30°C to about 100°C. For example, when subjected to thermal cycling testing as described herein, the ratio of the dielectric constant after thermal cycling to the initial dielectric constant can be about 0.8 or greater, about 0.9 or greater in some embodiments, and about 0.91 to about 0.99 in some embodiments. Likewise, the ratio of the dissipation after exposure to high temperature to the initial dissipation factor can be about 1 or less, in some embodiments about 0.95 or less, in some embodiments about 0.1 to about 0.9, and in some embodiments about 0.2 to about 0.8. The change in dissipation factor (i.e., initial dissipation factor - dissipation factor after thermal cycling) can also be in the range of about -0.1 to about 0.1, in some embodiments about -0.05 to about 0.01, and in some embodiments, about -0.001 to 0.
[0026] It is generally believed that polymer compositions exhibiting low dissipation factors and dielectric constants will not be laser activatable, and do not have sufficiently good thermal properties, mechanical properties, and ease of processing (i.e., low viscosity) to enable them to be used in certain types of applications. However, contrary to conventional thinking, it has been found that the polymer composition has excellent thermal properties, mechanical properties, and processability. The melting temperature of the composition may be, for example, from about 250°C to about 440°C, from about 270°C to about 400°C in some embodiments, and from about 300°C to about 380°C in some embodiments. Even at such a melting temperature, the ratio of the deflection temperature under load ("DTUL") (a measure of short-term heat resistance) to the melting temperature may still remain relatively high. For example, the ratio may be from about 0.5 to about 1.00, from about 0.6 to about 0.95 in some embodiments, and from about 0.65 to about 0.85 in some embodiments. Specific DTUL values may range, for example, from about 200° C. to about 350° C., in some embodiments from about 210° C. to about 320° C., and in some embodiments from about 230° C. to about 290° C. Such high DTUL values may allow the use of high-speed, reliable surface mount processes to mate the structure with other components of an electrical assembly, among other things.
[0027] The polymer composition may also have high impact strength, which is useful when forming thin substrates. For example, as measured according to ISO test number ISO 179-1:2010 at a temperature of 23°C, the composition may, for example, have a high impact strength of about 0.5 kJ / m 2 or higher, in some embodiments, from about 1 to about 50 kJ / m 2 , and in some embodiments, from about 2 to about 20 kJ / m 2The Charpy notched impact strength of the composition can also be good. The tensile and flexural mechanical properties of the composition can also be good. For example, the polymer composition can exhibit: a tensile strength of about 20 MPa to about 500 MPa, in some embodiments, about 50 MPa to about 400 MPa, and in some embodiments, about 70 MPa to about 350 MPa; a tensile strain at break of about 0.4% or more, in some embodiments, about 0.5% to about 10%, and in some embodiments, about 0.6% to about 3.5%; and / or a tensile modulus of about 5,000 MPa to about 20,000 MPa, in some embodiments, about 8,000 MPa to about 20,000 MPa, and in some embodiments, about 10,000 MPa to about 20,000 MPa. The tensile properties can be determined according to ISO test number 527:2012 at a temperature of 23°C. For example, the polymer composition may exhibit: a tensile strength of about 20 MPa to about 500 MPa, in some embodiments, about 50 MPa to about 400 MPa, and in some embodiments, about 100 MPa to about 350 MPa; a flexural elongation of about 0.4% or more, in some embodiments, about 0.5% to about 10%, and in some embodiments, about 0.6% to about 3.5%; and / or a flexural modulus of about 5,000 MPa to about 20,000 MPa, in some embodiments, about 8,000 MPa to about 20,000 MPa, and in some embodiments, about 10,000 MPa to about 15,000 MPa. Flexural properties may be determined according to 178:2010 at a temperature of 23°C. In addition, the polymer composition may also have a high impact strength, which may be useful when forming thin articles. For example, the polymer composition may have a flexural modulus of about 3 kJ / m 2 or higher, in some embodiments about 5 kJ / m 2 or higher, in some embodiments about 7 kJ / m 2 or higher, in some embodiments about 8 kJ / m 2 About 40 kJ / m 2 , and in some embodiments, about 10 kJ / m 2 About 25 kJ / m 2 The Charpy notched impact strength can be measured according to ISO test number ISO 179-1:2010 at a temperature of 23°C.
[0028] Due to the above properties, the polymer composition can be easily formed into a substrate, which can then be applied using a laser direct structuring process (LDS) together with one or more conductive elements. Due to the beneficial properties of the polymer composition, the resulting substrate can have very small dimensions, such as a thickness of about 5 mm or less, in some embodiments about 4 mm or less, and in some embodiments about 0.5 to about 3 mm. If desired, the conductive element can be an antenna (e.g., an antenna resonating element), so that the resulting component is an antenna structure that can be used in a variety of different electronic components (e.g., cellular phones, automotive equipment, etc.).
[0029] Various embodiments of the invention will now be described in further detail.
[0030] I. Polymer composition
[0031] A. Liquid Crystal Polymer
[0032] The polymer composition comprises one or more liquid crystal polymers, which are generally classified as "thermotropic" because the liquid crystal polymer can have a rod-like structure and exhibit crystallization behavior in its molten state (e.g., a thermotropic nematic state). The liquid crystal polymer used in the polymer composition generally has a melting temperature of about 200°C to about 400°C, in some embodiments, about 250°C to about 380°C, in some embodiments, about 270°C to about 360°C, and in some embodiments, about 300°C to about 350°C. The melting temperature can be determined using differential scanning calorimetry (DSC), such as by ISO test number 11357-3:2011, as is known in the art. Such polymers can be formed from one or more types of repeating units known in the art. For example, the liquid crystal polymer can include one or more aromatic ester repeating units generally represented by the following formula (I):
[0033]
[0034] in,
[0035] Ring B is a substituted or unsubstituted 6-membered aryl group (e.g., 1,4-phenylene or 1,3-phenylene), a substituted or unsubstituted 6-membered aryl group fused to a substituted or unsubstituted 5-membered or 6-membered aryl group (e.g., 2,6-naphthalene), or a substituted or unsubstituted 6-membered aryl group linked to a substituted or unsubstituted 5-membered or 6-membered aryl group (e.g., 4,4-biphenylene); and
[0036] Y1 and Y2 are independently O, C(O), NH, C(O)HN or NHC(O).
[0037] Typically, at least one of Y1 and Y2 is C(O). Examples of such aromatic ester repeating units may include, for example, aromatic dicarboxyl repeating units (Y1 and Y2 in Formula I are C(O)), aromatic hydroxycarboxyl repeating units (Y1 in Formula I is O, and Y2 is C(O)), and various combinations thereof.
[0038] For example, aromatic hydroxycarboxylic repeating units derived from aromatic hydroxycarboxylic acids can be used, such as 4-hydroxybenzoic acid; 4-hydroxy-4'-biphenylcarboxylic acid; 2-hydroxy-6-naphthoic acid; 2-hydroxy-5-naphthoic acid; 3-hydroxy-2-naphthoic acid; 2-hydroxy-3-naphthoic acid; 4'-hydroxyphenyl-4-benzoic acid; 3'-hydroxyphenyl-4-benzoic acid; 4'-hydroxyphenyl-3-benzoic acid, etc., as well as alkyl, alkoxy, aryl and halogen substitutes and combinations thereof. Particularly suitable aromatic hydroxycarboxylic acids are 4-hydroxybenzoic acid (HBA) and 6-hydroxy-2-naphthoic acid (HNA). When used, repeating units derived from hydroxycarboxylic acids (e.g., HBA and / or HNA) generally constitute about 20 mol.% or more of the polymer, about 25 mol.% or more in some embodiments, about 30 mol.% to 100 mol.% in some embodiments, and about 30 mol.% to about 60 mol.% in some embodiments.
[0039] Aromatic dicarboxyl repeating units derived from aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, 2,6-naphthalene dicarboxylic acid, diphenyl ether-4,4'-dicarboxylic acid, 1,6-naphthalene dicarboxylic acid, 2,7-naphthalene dicarboxylic acid, 4,4'-dicarboxybiphenyl, bis(4-carboxyphenyl)ether, bis(4-carboxyphenyl)butane, bis(4-carboxyphenyl)ethane, bis(3-carboxyphenyl)ether, bis(3-carboxyphenyl)ethane, and the like, as well as alkyl, alkoxy, aryl, and halogen substitutes thereof, and combinations thereof, may also be used. Particularly suitable aromatic dicarboxylic acids may include, for example, terephthalic acid (TA), isophthalic acid (IA), and 2,6-naphthalene dicarboxylic acid (NDA). When used, repeating units derived from aromatic dicarboxylic acids (e.g., IA, TA, and / or NDA) typically each constitute from about 1 mol.% to about 40 mol.%, in some embodiments, from about 2 mol.% to about 30 mol.%, and in some embodiments, from about 5 mol.% to about 25 mol.% of the polymer.
[0040] Other repeating units can also be used in the polymer.In certain embodiments, for example, it is possible to use repeating units derived from aromatic diols, such as hydroquinone, resorcinol, 2,6-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 4,4'-dimethylbiphenyl (or 4,4'-biphenol), 3,3'-dihydroxybiphenyl, 3,4'-dihydroxybiphenyl, 4,4'-dihydroxybiphenyl ether, bis (4-hydroxyphenyl) ethane, etc. and its alkyl, alkoxy, aryl and halogen substituents and combinations thereof. Particularly suitable aromatic diols can include, for example, hydroquinone (HQ) and 4,4'-biphenol (BP).When used, repeating units derived from aromatic diols (for example, HQ and / or BP) generally constitute about 1mol.% to about 50mol.%, about 2mol.% to about 40mol.% in some embodiments, and about 5mol.% to about 35mol.% in some embodiments of polymers. Repeating units, such as those derived from aromatic amides (e.g., acetaminophen (APAP) and / or aromatic amines (e.g., 4-aminophenol (AP), 3-aminophenol, 1,4-phenylenediamine, 1,3-phenylenediamine, etc.), may also be used. When used, repeating units derived from aromatic amides (e.g., APAP) and / or aromatic amines (e.g., AP) typically constitute from about 0.1 mol.% to about 20 mol.%, in some embodiments from about 0.5 mol.% to about 15 mol.%, and in some embodiments from about 1 mol.% to about 10 mol.% of the polymer. It should also be understood that various other monomer repeating units may be incorporated into the polymer. For example, in certain embodiments, the polymer may contain one or more repeating units derived from non-aromatic monomers (e.g., aliphatic or alicyclic hydroxycarboxylic acids, dicarboxylic acids, diols, amides, amines, etc.). Of course, in other embodiments, the polymer may be "wholly aromatic", i.e., it lacks repeating units derived from non-aromatic (e.g., aliphatic or alicyclic) monomers.
[0041] As described above, the liquid crystal polymer is typically a "high naphthalene" polymer because the liquid crystal polymer contains a relatively high content of repeating units derived from naphthalene hydroxycarboxylic acids and naphthalene dicarboxylic acids (e.g., NDA, HNA) or a combination thereof. That is, the total amount of repeating units derived from naphthalene hydroxycarboxylic acids and / or naphthalene dicarboxylic acids (e.g., NDA, HNA, or a combination of HNA and NDA) is typically about 10 mol.% or more of the polymer, in some embodiments about 12 mol.% or more, in some embodiments about 15 mol.% or more, in some embodiments about 18 mol.% or more, in some embodiments about 30 mol.% or more, in some embodiments about 40 mol.% or more, in some embodiments about 45 mol.% or more, in some embodiments about 50 mol.% or more, in some embodiments about 60 mol.% or more, in some embodiments 62 mol.% or more, in some embodiments about 68 mol.% or more, in some embodiments 70 mol.% or more, and in some embodiments from about 70 mol.% to about 80 mol.%.
[0042] For example, in one embodiment, the repeating unit derived from HNA can constitute about 30mol.% or more of the polymer, about 40mol.% or more in some embodiments, about 45mol.% or more in some embodiments, 50mol.% or more in some embodiments, about 60mol.% or more in some embodiments, about 62mol.% or more in some embodiments, about 68mol.% or more in some embodiments, about 70mol.% or more in some embodiments, and about 70mol.% to about 80mol.%. Liquid crystal polymers can also include various other monomers. For example, the polymer can include a repeating unit derived from HBA, and its content is about 10mol.% to about 40mol.%, about 15mol.% to about 35mol.% in some embodiments, and about 20mol.% to about 30mol.% in some embodiments. When used, the molar ratio of HNA to HBA can be selectively controlled within a specific range to help achieve the desired properties, such as about 0.1 to about 40, about 0.5 to about 20 in some embodiments, about 0.8 to about 10 in some embodiments, and about 1 to about 5 in some embodiments. The polymer may also contain: aromatic dicarboxylic acids (e.g., IA and / or TA) in an amount of about 1 mol.% to about 40 mol.%, and in some embodiments, about 5 mol.% to about 25 mol.%; and / or aromatic diols (e.g., BP and / or HQ) in an amount of about 1 mol.% to about 40 mol.%, and in some embodiments, about 5 mol.% to about 25 mol.%. However, in some cases, it may be desirable to minimize the presence of such monomers in the polymer to help achieve the desired properties. For example, the total amount of aromatic dicarboxylic acids (e.g., IA and / or TA) may be about 20 mol% or less of the polymer, in some embodiments, about 15 mol.% or less, in some embodiments, about 10 mol.% or less, in some embodiments, 0 mol.% to about 5 mol.%, and in some embodiments, 0 mol.% to about 2 mol.%. Similarly, the total amount of aromatic dicarboxylic acids (e.g., IA and / or TA) can be about 20 mol% or less, in some embodiments, about 15 mol% or less, in some embodiments, about 10 mol% or less, in some embodiments, 0 mol% to about 5 mol%, and in some embodiments, 0 mol% to about 2 mol% (e.g., 0 mol%) of the polymer.
[0043] In another embodiment, the repeating unit derived from NDA can constitute 10 mol.% or more of the polymer, in some embodiments about 12 mol.% or more, in some embodiments about 15 mol.% or more, and in some embodiments about 18 mol.% to about 95 mol.%. In such an embodiment, the liquid crystal polymer may also include various other monomers, such as: aromatic hydroxycarboxylic acid (e.g., HBA), whose content is about 20 mol.% to about 60 mol.%, and in some embodiments about 30 mol.% to about 50 mol.%; aromatic dicarboxylic acid (e.g., IA and / or TA), whose content is about 2 mol.% to about 30 mol.%, and in some embodiments about 5 mol.% to about 25 mol.%; and / or aromatic diol (e.g., BP and / or HQ), whose content is about 2 mol.% to about 40 mol.%, and in some embodiments about 5 mol.% to about 35 mol.%.
[0044] In general, the total amount of liquid crystal polymer used in the polymer composition is about 40wt.% to about 99.5wt.%, about 50wt.% to about 99wt.% in some embodiments, about 60wt.% to about 98wt.% in some embodiments, and about 70wt.% to about 95wt.% in some embodiments. In certain embodiments, all liquid crystal polymers are "high naphthalene" polymers as described above. However, in other embodiments, "low naphthalene" liquid crystal polymers can also be used in the composition, wherein the total amount of repeating units derived from naphthalene hydroxycarboxylic acid and / or naphthalene dicarboxylic acid (e.g., NDA, HNA or a combination of HNA and NDA) is less than 10mol.% of the polymer, about 8mol.% or less in some embodiments, about 6mol.% or less in some embodiments, and about 1mol.% to about 5mol.% in some embodiments. When used, it is generally desired that such low naphthalene polymers are present only in relatively low amounts. For example, low naphthalene liquid crystal polymers, when used, typically constitute from about 1 wt.% to about 50 wt.%, in some embodiments from about 2 wt.% to about 40 wt.%, and in some embodiments from about 5 wt.% to about 30 wt.%, of the total amount of liquid crystal polymers in the composition, and constitute from about 0.5 wt.% to about 45 wt.%, in some embodiments from about 2 wt.% to about 35 wt.%, and in some embodiments from about 5 wt.% to about 25 wt.% of the entire composition. In contrast, high naphthalene liquid crystal polymers typically constitute from about 50 wt.% to about 99 wt.%, in some embodiments from about 60 wt.% to about 98 wt.%, and in some embodiments from about 70 wt.% to about 95 wt.%, of the total amount of liquid crystal polymers in the composition, and constitute from about 55 wt.% to about 99.5 wt.%, in some embodiments from about 65 wt.% to about 98 wt.%, and in some embodiments from about 75 wt.% to about 95 wt.% of the entire composition.
[0045] B. Laser-activatable additives
[0046] The polymer composition is "laser-activatable" because it contains an additive that can be activated by a laser direct structuring (LDS) process. In such a process, the additive is exposed to a laser that causes the metal to be released. Therefore, the laser draws the pattern of the conductive element onto the component and leaves a rough surface containing embedded metal particles. These particles act as nuclei for crystal growth in subsequent plating processes (e.g., copper plating, gold plating, nickel plating, silver plating, zinc plating, tin plating, etc.). Laser-activatable additives generally constitute about 0.1wt.% to about 20wt.% of the polymer composition, about 0.5wt.% to about 15wt.% in some embodiments, and about 1wt.% to about 10wt.% in some embodiments. Laser-activatable additives generally include spinel crystals, which may include two or more metal oxide cluster structures within a definable crystal form. For example, the entire crystal form may have the following general formula:
[0047] AB2O4
[0048] in,
[0049] A is a divalent metal cation, such as cadmium, chromium, manganese, nickel, zinc, copper, cobalt, iron, magnesium, tin, titanium, etc. and combinations thereof; and
[0050] B is a trivalent metal cation, such as chromium, iron, aluminum, nickel, manganese, tin, etc. and combinations thereof.
[0051] In general, A in the above formula provides the main cationic component of the first metal oxide cluster, and B provides the main cationic component of the second metal oxide cluster. These oxide clusters can have the same or different structures. In one embodiment, for example, the first metal oxide cluster has a tetrahedral structure, and the second metal oxide cluster has an octahedral cluster. In any case, these clusters can provide together a single identifiable crystal type structure with improved sensitivity to electromagnetic radiation. The example of suitable spinel crystals includes, for example, MgAl2O4, ZnAl2O4, FeAl2O4, CuFe2O4, CuCr2O4, MnFe2O4, NiFe2O4, TiFe2O4, FeCr2O4, MgCr2O4, etc. Copper chromium oxide (CuCr2O4) is particularly suitable for the present invention and can be obtained from ShepherdColor company with the name "Shepherd Black 1GM".
[0052] C. Fiber filler
[0053] Fibrous fillers can also be used in polymer compositions to improve the thermal and mechanical properties of the composition without significantly affecting electrical properties. Fibrous fillers typically include fibers having a high tensile strength relative to their mass. For example, the ultimate tensile strength of the fibers (determined according to ASTM D2101) is typically from about 1000 to about 15000 megapascals (MPa), in some embodiments from about 2000 MPa to about 10000 MPa, and in some embodiments from about 3000 MPa to about 6000 MPa. To help maintain the desired dielectric properties, such high-strength fibers can be formed from materials that generally have insulating properties, such as glass, ceramics (e.g., alumina or silica), aramid (e.g., sold by EI duPont de Nemours) and / or polyesters. Wilmington, Delaware) polyolefins, polyesters, etc. Glass fibers are particularly suitable, such as E-glass, A-glass, C-glass, D-glass, AR-glass, R-glass, S1-glass, S2-glass, etc.
[0054] In addition, although the fibers used in the fiber filler can have a variety of different sizes, fibers with a certain aspect ratio can help improve the mechanical properties of the resulting polymer composition. That is, the aspect ratio (average length divided by the nominal diameter) is about 2 or more, about 4 or more in some embodiments, about 5 to about 50 in some embodiments, and about 8 to about 40 in some embodiments. The fiber filler can, for example, have a weight average length of about 10 microns or more, about 25 microns or more in some embodiments, about 50 microns or more to about 800 microns or less in some embodiments, and about 60 microns to about 500 microns in some embodiments. In addition, this fiber filler can, for example, have a volume average length of about 10 microns or more, about 25 microns or more in some embodiments, about 50 microns or more to about 800 microns or less in some embodiments, and about 60 microns to about 500 microns in some embodiments. The fibrous filler may also have a nominal diameter of about 5 microns or greater, in some embodiments about 6 microns or greater, in some embodiments about 8 microns to about 40 microns, and in some embodiments about 9 microns to about 20 microns. The relative amount of the fibrous filler may also be selectively controlled to help achieve the desired mechanical and thermal properties without adversely affecting other properties of the polymer composition, such as its flowability and dielectric properties. For example, a sufficient amount of fibrous filler may be used so that the weight ratio of fibrous filler to laser-activatable additive is from about 1 to about 5, in some embodiments about 1.5 to about 4.5, and in some embodiments about 2 to about 3.5. For example, the fibrous filler may constitute from about 1 wt.% to about 40 wt.%, in some embodiments about 3 wt.% to about 30 wt.%, and in some embodiments about 5 wt.% to about 20 wt.% of the polymer composition.
[0055] D. Hydrophobic materials
[0056] If desired, additional hydrophobic materials may be used in the polymer composition to help further reduce the tendency of the polymer composition to absorb water, which can help stabilize the dielectric constant and dissipation factor in the high frequency range. When used, the weight ratio of one or more liquid crystal polymers to one or more hydrophobic materials is generally from about 1 to about 20, in some embodiments from about 2 to about 15, and in some embodiments from about 3 to about 10. For example, the hydrophobic material may constitute from about 1 wt.% to about 60 wt.%, in some embodiments from about 2 wt.% to about 50 wt.%, and in some embodiments from about 5 wt.% to about 40 wt.% of the entire polymer composition.
[0057] Particularly suitable hydrophobic materials are low surface energy elastomers, such as fluoropolymers, silicone polymers, etc. For example, fluoropolymers may include hydrocarbon backbone polymers in which some or all of the hydrogen atoms are replaced by fluorine atoms. The backbone polymer may be a polyolefin and formed by fluorine-substituted unsaturated olefin monomers. Fluoropolymers may be a homopolymer of this fluorine-substituted monomer or a copolymer of fluorine-substituted monomers or a mixture of fluorine-substituted monomers and non-fluorine-substituted monomers. Except for fluorine atoms, fluoropolymers may also be replaced by other halogen atoms (such as chlorine atoms and bromine atoms). Representative monomers suitable for forming fluoropolymers for the present invention are tetrafluoroethylene (TFE), vinylidene fluoride (VF2), hexafluoropropylene (HFP), chlorotrifluoroethylene (CTFE), perfluoroethylvinyl ether (PEVE), perfluoromethylvinyl ether (PMVE), perfluoropropylvinyl ether (PPVE), etc. and mixtures thereof. Specific examples of suitable fluorine-containing polymers include polytetrafluoroethylene (PTFE), perfluoroalkyl vinyl ether (PVE), poly(tetrafluoroethylene-co-perfluoroalkyl vinyl ether) (PFA), fluorinated ethylene-propylene copolymer (FEP), ethylene-tetrafluoroethylene copolymer (ETFE), polyvinylidene fluoride (PVDF), polychlorotrifluoroethylene (PCTFE) and copolymers of TFE with VF2 and / or HFP, etc., and mixtures thereof.
[0058] In certain embodiments, hydrophobic material (such as fluoropolymer) can have the particle size that selectively controls to help form the film of relatively low thickness.For example, as measured according to ISO 13320:2009 using laser diffraction technology (such as using HoribaLA-960 particle size distribution analyzer), the median particle size (such as diameter) of hydrophobic material can be about 1 micron to about 60 microns, about 2 microns to about 55 microns in some embodiments, about 3 microns to about 50 microns in some embodiments, and about 25 microns to about 50 microns in some embodiments.Hydrophobic material can also have narrow size distribution.That is to say, at least about 70 volume % of particles, at least about 80 volume % of particles in some embodiments and at least about 90 volume % of particles in some embodiments can have the size in the above-mentioned range.
[0059] E. Hollow filler
[0060] Although it is by no means necessary, the polymer composition may also include one or more hollow inorganic fillers to help achieve the desired dielectric constant. For example, the dielectric constant of this filler at 100MHz can be about 3.0 or less, about 2.5 or less in some embodiments, about 1.1 to about 2.3 in some embodiments, and about 1.2 to about 2.0 in some embodiments. The hollow inorganic filler has an internal hollow space or cavity and can be synthesized using techniques known in the art. The hollow inorganic filler can be made of conventional materials. For example, the hollow inorganic filler can include aluminum oxide, silicon dioxide, zirconium oxide, magnesium oxide, glass, fly ash, borate, phosphate, ceramic, etc. In one embodiment, the hollow inorganic filler can include hollow glass fillers, hollow ceramic fillers and mixtures thereof. In one embodiment, the hollow inorganic filler includes a hollow glass filler. The hollow glass filler can be made of soda-lime borosilicate glass, soda-lime glass, borosilicate glass, sodium borosilicate glass, sodium silicate glass or aluminosilicate glass. In this regard, in one embodiment, the composition of the glass, although not limited, can be at least about 65wt.% SiO2, 3wt.%-15wt.% Na2O, 8wt.%-15wt.% CaO, 0.1wt.%-5wt.% MgO, 0.01wt.%-3wt.% Al2O3, 0.01wt.%-1wt.% K2O, and optional other oxides (e.g., Li2O, Fe2O3, TiO2, B2O3). In another embodiment, the composition can be about 50wt.% to 58wt.% SiO2, 25wt.% to 30wt.% Al2O3, 6wt.% to 10wt.% CaO, 1wt.% to 4wt.% Na2O / K2O, and 1wt.% to 5wt.% other oxides. In addition, in one embodiment, the hollow glass filler can include more alkaline earth metal oxides than alkali metal oxides. For example, the weight ratio of alkaline earth metal oxide to alkali metal oxide may be greater than 1, in some embodiments about 1.1 or greater, in some embodiments about 1.2 to about 4, and in some embodiments about 1.5 to about 3. Regardless of the foregoing, it should be understood that the glass composition may vary depending on the type of glass used and still provide the desired benefits of the present invention.
[0061] Hollow inorganic filler can have at least one size, and the average value of size is about 1 micron or more, about 5 microns or more in some embodiments, about 8 microns or more in some embodiments, about 1 micron to about 150 microns in some embodiments, about 10 microns to about 150 microns in some embodiments, and about 12 microns to about 50 microns in some embodiments. In one embodiment, such average value can refer to d50 value. In addition, the D10 of hollow inorganic filler can be about 3 microns or more, about 4 microns or more in some embodiments, about 5 microns to about 20 microns in some embodiments, and about 6 microns to about 15 microns in some embodiments. The D90 of hollow inorganic filler can be about 10 microns or more, about 15 microns or more in some embodiments, about 20 microns to about 150 microns in some embodiments, and about 22 microns to about 50 microns in some embodiments. In this regard, hollow inorganic filler can exist according to the following size distribution: it can be Gaussian size distribution, normal size distribution or non-normal size distribution. In one embodiment, hollow inorganic filler can have Gaussian size distribution. In another embodiment, the hollow inorganic filler may have a normal size distribution. In other embodiments, the hollow inorganic filler may have a non-normal size distribution. Examples of non-normal size distribution may include unimodal and multimodal (e.g., bimodal) size distributions. When referring to the above-mentioned size, this size may be any size. However, in one embodiment, this size refers to diameter. For example, this value of size refers to the average diameter of a sphere. Size, such as average diameter, may be determined according to 3M QCM 193.0. In this regard, in one embodiment, the hollow inorganic filler may refer to a hollow sphere, such as a hollow glass sphere. For example, the hollow inorganic filler may have an average aspect ratio of about 1. Typically, the average aspect ratio may be about 0.8 or greater, about 0.85 or greater in some embodiments, about 0.9 to about 1.3 in some embodiments, and about 0.95 to about 1.05 in some embodiments.
[0062] In addition, the hollow inorganic filler can have a relatively thin wall to help the dielectric properties of the polymer composition and the reduction of weight. The thickness of the wall can be about 50% or less of the average size of the hollow inorganic filler, such as the average diameter, in some embodiments, about 40% or less, in some embodiments, about 1% to about 30%, and in some embodiments, about 2% to about 25%. In addition, the hollow inorganic filler can have a certain true density, which can make it easy to handle and provide a polymer composition with reduced weight. Generally, the true density refers to the quotient obtained by dividing the mass of the hollow filler sample by the true volume of the pile of hollow fillers, where the true volume is referred to as the total volume of the hollow fillers. In this regard, the true density of the hollow inorganic filler can be about 0.1g / cm 3 or greater, in some embodiments about 0.2 g / cm3 or greater, in some embodiments, about 0.3 g / cm 3 or greater to about 1.2 g / cm 3 , and in some embodiments, about 0.4 g / cm 3 or greater to about 0.9 g / cm 3 The true density can be determined according to 3M QCM 14.24.1.
[0063] Even though the fillers are hollow, they can have mechanical strength such that the structural integrity of the filler is maintained, resulting in a lower likelihood of the filler breaking during processing and / or use. In this regard, the isotactic crush resistance of the hollow inorganic filler (i.e., wherein at least 80 vol.%, such as at least 90 vol.% of the hollow filler remains) can be about 20 MPa or more, in some embodiments about 100 MPa or more, in some embodiments about 150 MPa to about 500 MPa, and in some embodiments about 200 MPa to about 350 MPa. The isotactic crush resistance can be determined according to 3M QCM 14.1.8.
[0064] The basicity of the hollow inorganic filler can be about 1.0meq / g or less, about 0.9meq / g or less in some embodiments, about 0.1meq / g to about 0.8meq / g in some embodiments, and about 0.2meq / g to about 0.7meq / g in some embodiments. Basicity can be measured according to 3M QCM 55.19. In order to provide relatively low basicity, the hollow inorganic filler can be treated with suitable acid such as phosphoric acid. In addition, the hollow inorganic filler can also include surface treatment to help provide better compatibility with the polymer and / or other components in the polymer composition. For example, the surface treatment can be silanization. In particular, the surface treatment agent can include but is not limited to aminosilane, epoxy silane, etc.
[0065] When used, the hollow inorganic filler may, for example, constitute about 1 wt.% or more, in some embodiments about 4 wt.% or more, in some embodiments about 5 wt.% to about 40 wt.%, and in some embodiments about 10 wt.% to about 30 wt.% of the polymer composition.
[0066] F. Granular filler
[0067] If desired, particulate fillers can be used to improve certain properties of the polymer composition. Particulate fillers can be used in the polymer composition, and the amount of particulate fillers is about 5 parts by weight to about 60 parts by weight per 100 parts by weight of the liquid crystal polymer used in the polymer composition, about 10 parts by weight to about 50 parts by weight in some embodiments, and about 15 parts by weight to about 40 parts by weight in some embodiments. For example, the particulate filler can constitute about 5wt.% to about 50wt.%, about 10wt.% to about 40wt.% in some embodiments, and about 15wt.% to about 30wt.% of the polymer composition.
[0068] In certain embodiments, particles having a certain hardness value may be used to help improve the surface properties of the composition. For example, based on the Mohs hardness scale, the hardness value may be about 2 or greater, in some embodiments about 2.5 or greater, in some embodiments about 3 to about 11, in some embodiments about 3.5 to about 11, and in some embodiments about 4.5 to about 6.5. Examples of such particles may include, for example, silica (Mohs hardness of 7), mica (e.g., Mohs hardness of about 3); carbonates, such as calcium carbonate (CaCO3, Mohs hardness of 3.0) or copper carbonate hydroxide (Cu2CO3(OH)2, Mohs hardness of 4.0); fluorides, such as calcium fluoride (CaFl2, Mohs hardness of 4.0); phosphates, such as calcium pyrophosphate ((Ca2P2O7, Mohs hardness of 5.0), anhydrous calcium hydrogen phosphate ( CaHPO4, Mohs hardness is 3.5) or hydrated aluminum phosphate (AlPO4·2H2O, Mohs hardness is 4.5); borates, such as calcium hydroxide borosilicate (Ca2B5SiO9(OH)5, Mohs hardness is 3.5); alumina (AlO2, Mohs hardness is 10.0); sulfates, such as calcium sulfate (CaSO4, Mohs hardness is 3.5) or barium sulfate (BaSO4, Mohs hardness is 3 to 3.5); etc., and combinations thereof.
[0069] The shape of the particle can be changed as needed. For example, in certain embodiments, flaky particles can be used, which have a relatively high aspect ratio (e.g., average diameter divided by average thickness), for example, about 10:1 or greater, about 20:1 or greater in some embodiments, and about 40:1 to about 200:1 in some embodiments. For example, as measured using laser diffraction technology (e.g., using Horiba LA-960 particle size distribution analyzer) according to ISO 13320:2009, the average diameter of the particle can be about 5 microns to about 200 microns, about 30 microns to about 150 microns in some embodiments, and about 50 microns to about 120 microns in some embodiments. Suitable flaky particles can be formed by natural and / or synthetic silicate minerals, such as mica, halloysite, kaolinite, illite, montmorillonite, vermiculite, palygorskite, pyrophyllite, calcium silicate, aluminum silicate, wollastonite, etc. For example, mica is particularly suitable. Generally any form of mica can be used, including, for example, muscovite (KAl2(AlSi3)O 10 (OH)2), biotite (K(Mg,Fe)3(AlSi3)O 10 (OH)2), phlogopite (KMg3(AlSi3)O 10 (OH)2), lepidolite (K(Li,Al) 2-3 (AlSi3)O 10 (OH)2), glauconite (K,Na)(Al,Mg,Fe)2(Si,Al)4O 10 (OH) 2) and the like. Granular particles may also be used. Typically, such particles have an average diameter of about 0.1 to about 10 microns, in some embodiments about 0.2 to about 4 microns, and in some embodiments about 0.5 to about 2 microns, as measured using laser diffraction techniques (e.g., using a Horiba LA-960 particle size distribution analyzer) according to ISO 13320:2009. Particularly suitable particulate fillers may include, for example, talc, barium sulfate, calcium sulfate, calcium carbonate, and the like.
[0070] The granular filler can be mainly or completely formed by one kind of particle, such as flaky particles (e.g., mica) or granular particles (e.g., barium sulfate). That is, such flaky particles or granular particles can constitute about 50wt.% or more of the granular filler, and in some embodiments about 75wt.% or more (e.g., 100wt.%). Of course, in other embodiments, flaky particles and granular particles can also be used in combination. In such embodiments, for example, flaky particles can constitute about 0.5wt.% to about 20wt.% of the granular filler, and in some embodiments about 1wt.% to about 10wt.%, and granular particles constitute about 80wt.% to about 99.5wt.% of the granular filler, and in some embodiments about 90wt.% to about 99wt.%.
[0071] If desired, particles may also be coated with fluorinated additives to help improve the processing of the composition, for example, by providing better mold filling, internal lubrication, demoulding, etc. Fluorinated additives may include fluoropolymers containing hydrocarbon backbone polymers in which some or all of the hydrogen atoms are replaced by fluorine atoms. The backbone polymer may be a polyolefin and formed by fluorine-substituted unsaturated olefin monomers. Fluorinated polymers may be a homopolymer of this fluorine-substituted monomer or a copolymer of fluorine-substituted monomers or a mixture of fluorine-substituted monomers and non-fluorine-substituted monomers. In addition to fluorine atoms, fluoropolymers may also be replaced by other halogen atoms (such as chlorine atoms and bromine atoms). Representative monomers suitable for forming fluoropolymers used in the present invention are tetrafluoroethylene, vinylidene fluoride, hexafluoropropylene, chlorotrifluoroethylene, perfluoroethyl vinyl ether, perfluoromethyl vinyl ether, perfluoropropyl vinyl ether, etc., and mixtures thereof. Specific examples of suitable fluorine-containing polymers include polytetrafluoroethylene, perfluoroalkyl vinyl ether, poly(tetrafluoroethylene-co-perfluoroalkyl vinyl ether), fluorinated ethylene-propylene copolymers, ethylene-tetrafluoroethylene copolymers, polyvinylidene fluoride, polychlorotrifluoroethylene, and the like, and mixtures thereof.
[0072] G. Other additives
[0073] A variety of additional additives may also be included in the polymer composition, such as lubricants, thermally conductive fillers, pigments, antioxidants, stabilizers, surfactants, waxes, flame retardants, anti-drip additives, nucleating agents (e.g., boron nitride), flow modifiers (e.g., aluminum hydroxide), dielectric materials, and other materials added to enhance performance and processability. For example, when used, lubricants and / or flow modifiers may constitute from about 0.05 wt.% to about 5 wt.% of the polymer composition and in some embodiments from about 0.1 wt.% to about 1 wt.%.
[0074] In some embodiments, dielectric materials may be optionally used to help adjust the dielectric constant to a desired range. For example, dielectric materials typically have a dielectric constant of about 0.1 ohm-cm to about 1×10 12 ohm-cm, in some embodiments, from about 0.5 ohm-cm to about 1×10 11 ohm-cm, in some embodiments, from about 1 ohm-cm to about 1x10 10 ohm-cm, and in some embodiments, from about 2 ohm-cm to about 1 x 10 8ohm-cm volume resistivity. This can be achieved by selecting a single material with the desired volume resistivity, or by blending multiple materials together (e.g., insulating materials and conductive materials) so that the resulting blend has the desired volume resistivity. In one embodiment, for example, inorganic oxide materials that can exhibit a linear response of charge (or polarization) to voltage can be used. These materials can exhibit fully reversible charge polarization within the crystal structure after the applied electric field is removed. Suitable inorganic oxide materials for this purpose may include, for example, ferroelectric and / or paraelectric materials. Examples of suitable ferroelectric materials include, for example, barium titanate (BaTiO3), strontium titanate (SrTiO3), calcium titanate (CaTiO3), magnesium titanate (MgTiO3), barium strontium titanate (SrBaTiO3), sodium barium niobate (NaBa2Nb5O 15 ), potassium barium niobate (KBa2Nb5O 15 ), calcium zirconate (CaZrO3), sphene (CaTiSiO5) and combinations thereof. Examples of suitable paraelectric materials also include, for example, titanium dioxide (TiO2), tantalum pentoxide (Ta2O5), hafnium dioxide (HfO2), niobium pentoxide (Nb2O5), aluminum oxide (Al2O3), zinc oxide (ZnO), etc. and combinations thereof. Particularly suitable inorganic oxide materials are particles including TiO2, BaTiO3, SrTiO3, CaTiO3, MgTiO3, BaSrTi2O6 and ZnO. Of course, other types of inorganic oxide materials (such as mica) can also be used as dielectric materials. Carbon materials such as graphite, carbon black, etc. can also be used.
[0075] Various techniques may be employed to help achieve the desired volume resistivity. In one embodiment, for example, an inorganic oxide material having a volume resistivity of 0.1 ohm-cm to about 500 ohm-cm, in some embodiments about 0.5 ohm-cm to about 250 ohm-cm, in some embodiments about 1 ohm-cm to about 100 ohm-cm, and in some embodiments about 2 ohm-cm to about 50 ohm-cm, as determined according to ASTM D257-14 at a temperature of about 20° C. may be employed. In another embodiment, for example, a carbon material having a volume resistivity of 1×10 3 ohm-cm to about 1×10 12 ohm-cm, in some embodiments about 1×10 4 ohm-cm to about 1×10 11 ohm-cm, in some embodiments about 1×10 5 ohm-cm to about 1×10 10ohm-cm, and in some embodiments, about 1×10 6 ohm-cm to about 1×10 8 ohm-cm.
[0076] Of course, as described above, conductive materials may also be used in combination with insulating materials to help achieve the desired volume resistivity of the dielectric material. Conductive materials typically have a resistivity of less than about 0.1 ohm-cm, and in some embodiments, about 1x10 -8 About 1x10 -2 ohm-cm, and insulating materials generally have a volume resistivity greater than about 1×10 12 ohm-cm, and in some embodiments about 1×10 13 About 1×10 18 ohm-cm volume resistivity. Suitable conductive materials may include, for example, conductive carbon materials (e.g., graphite, carbon black, fibers, graphene, nanotubes, etc.), metals, etc. Suitable insulating materials may also include inorganic oxide materials (e.g., particles) as described above, such as titanium dioxide (TiO2). When used, the weight percentage of the insulating material in the polymer composition to the weight percentage of the conductive material in the composition may be about 3 to about 100, in some embodiments about 3 to about 50, in some embodiments about 3 to about 20, in some embodiments about 7 to about 18, and in some embodiments about 8 to about 15. For example, the conductive material may constitute about 1 wt.% to about 20 wt.% of the dielectric material, in some embodiments about 3 wt.% to about 18 wt.%, and in some embodiments about 5 wt.% to about 15 wt.%, and the insulating material may constitute about 80 wt.% to about 99 wt.% of the dielectric material, in some embodiments 82 wt.% to about 97 wt.%, and in some embodiments about 85 wt.% to about 95 wt.%.
[0077] Regardless of the material used, it is generally desirable that the dielectric material be used only in relatively small concentrations so that the polymer composition can maintain the desired low dielectric constant. Thus, when used, the dielectric material typically constitutes about 10 wt.% or less of the polymer composition, in some embodiments about 5 wt.% or less, and in some embodiments about 0.001 wt.% to about 2 wt.%. In fact, in some embodiments, the polymer composition is generally free of such dielectric materials.
[0078] II. form
[0079] The components for forming the polymer composition can be combined together using any of a variety of different techniques known in the art. In a specific embodiment, for example, a liquid crystal polymer, a laser-activatable additive, and other optional additives are melt-processed as a mixture in an extruder to form a polymer composition. The mixture can be melt-kneaded in a single screw or multi-screw extruder at a temperature of about 250°C to about 450°C. In one embodiment, the mixture can be melt-processed in an extruder comprising multiple temperature zones. The temperature of each zone is typically set at about -60°C to about 25°C relative to the melting temperature of the polymer. For example, a twin-screw extruder (e.g., a Leistritz 18mm co-rotating fully meshing twin-screw extruder) can be used to melt-process the mixture. A universal screw design can be used to melt-process the mixture. In one embodiment, a mixture comprising all components can be fed to a feed throat in a first barrel by a volumetric feeder. In another embodiment, as known, different components can be added at different addition points in an extruder. For example, a liquid crystal polymer may be applied at the feed throat, and certain additives (e.g., dielectric materials, laser-activatable additives, and optional fibrous fillers) may be supplied at the same or different temperature zones downstream thereof. In any case, the resulting mixture may be melted and mixed and then extruded through a die. The extruded polymer composition may then be quenched and cured in a water bath and pelletized in a pelletizer and then dried.
[0080] The melt viscosity of the resulting composition is generally low enough that it can easily flow into the cavity of the mold to form a small-sized circuit substrate. For example, in a specific embodiment, the melt viscosity of the composition is generally low enough that it can easily flow into the cavity of the mold to form a small-sized circuit substrate. -1 The melt viscosity of the polymer composition can be about 500 Pa-s or less, in some embodiments about 250 Pa-s or less, in some embodiments about 5 Pa-s to about 150 Pa-s, in some embodiments about 5 Pa-s to about 100 Pa-s, in some embodiments about 10 Pa-s to about 100 Pa-s, in some embodiments about 15 Pa-s to about 90 Pa-s, as measured at a shear rate of about 1.5 % to about 2.0 % of the melt viscosity. The melt viscosity can be determined according to 11443:2005.
[0081] III. substrate
[0082] Once formed, the polymer composition can be molded into the desired shape of the substrate for the antenna system. Due to the beneficial properties of the polymer composition, the resulting substrate can have a very small size, such as a thickness of about 5 mm or less, about 4 mm or less in some embodiments, and about 0.5 to about 3 mm in some embodiments. Typically, the molded parts are molded using a single-component injection molding process, in which dried and preheated plastic particles are injected into the mold. Conductive elements can be formed in a variety of ways, such as by plating, electroplating, laser direct molding, etc. For example, when spinel crystals are included as laser-activatable additives, laser activation can cause the spinel crystals to crack and release the physical and chemical reaction of metal atoms. These metal atoms can serve as cores for metallization (e.g., reduction copper plating). The laser also produces a microscopic irregular surface and ablates the polymer matrix, producing many microscopic pits and undercuts, and copper can be anchored in these microscopic pits and undercuts during the metallization process.
[0083] If desired, the conductive element can be an antenna element (e.g., an antenna resonant element), so that the resulting portion forms an antenna system. The conductive element can form a variety of different types of antennas, such as antennas with resonant elements formed by: patch antenna elements, inverted-F antenna elements, closed and open slot antenna elements, loop antenna elements, monopoles, dipoles, planar inverted-F antenna elements, hybrids of these designs, and the like. The resulting antenna system can be used in a variety of different electronic components. As an example, the antenna system can be formed in an electronic component, such as a desktop computer, a portable computer, a handheld electronic device, an automotive device, and the like. In a suitable configuration, the antenna system is formed in a relatively compact housing of a portable electronic component with relatively small available internal space. Examples of suitable portable electronic components include cellular phones, laptop computers, small portable computers (e.g., ultraportable computers, netbook computers, and tablet computers), watch devices, pendant devices, earphone and receiver devices, media players with wireless communication capabilities, handheld computers (sometimes also referred to as personal digital assistants), remote controls, global positioning system (GPS) devices, handheld gaming devices, and the like. The antenna can also be integrated with other components, such as a camera module, a speaker, or a battery cover for a handheld device.
[0084] A particularly suitable electronic assembly is shown in Figure 1 and Figure 2 In FIG. 1 , a handheld device 10 having cellular telephone capabilities is shown. Figure 1As shown, device 10 may have a housing 12 formed of plastic, metal, other suitable dielectric materials, other suitable conductive materials, or a combination of such materials. Display 14 may be disposed on a front surface of device 10, such as a touch screen display. Device 10 may also have a speaker port 40 and other input-output ports. One or more buttons 38 and other user input devices may be used to collect user input. Figure 2 As shown, antenna system 26 is also disposed on rear surface 42 of device 10, although it should be understood that the antenna system may generally be located at any desired location on the device. The antenna system may be electrically connected to other components within the electronic device using any of a variety of known techniques. Referring again to FIG. Figure 1 to Figure 2 , housing 12 or a portion of housing 12 can act as a conductive ground plane for antenna system 26. Figure 3 , which shows antenna system 26 being fed by RF source 52 at positive antenna feed terminal 54 and ground antenna feed terminal 56. Positive antenna feed terminal 54 may be coupled to antenna resonating element 58, and ground antenna feed terminal 56 may be coupled to ground element 60. Resonating element 58 may have main arm 46 and shorting branch 48 connecting main arm 46 to ground 60.
[0085] Various other configurations for electrically connecting the antenna system are also contemplated. Figure 4 In the embodiment, the antenna system is based on a monopole antenna configuration and the resonant element 58 has a meandering serpentine path shape. In such an embodiment, the feed terminal 54 can be connected to one end of the resonant element 58, and the ground feed terminal 56 can be coupled to the housing 12 or another suitable ground plane element. Figure 5 In another embodiment shown, conductive antenna element 62 is configured to define a closed slot 64 and an open slot 66. Positive antenna feed terminal 54 and ground antenna feed terminal 56 may be used to feed the antenna formed by structure 62. In this type of arrangement, slots 64 and 66 act as antenna resonating elements for antenna element 26. The dimensions of slots 64 and 66 may be configured such that antenna element 26 operates in a desired communications frequency band (e.g., 2.4 GHz and 5 GHz, etc.). Another possible configuration of antenna system 26 is as follows: Figure 6 In this embodiment, antenna element 26 has a patch antenna resonating element 68 and may be fed using positive antenna feed terminal 54 and ground antenna feed terminal 56. Ground 60 may be associated with housing 12 or other suitable ground plane element in device 10. Figure 7Yet another illustrative configuration is shown that may be used for an antenna element of antenna system 26. As shown, antenna resonating element 58 has two main arms 46A and 46B. Arm 46A is shorter than arm 46B and is therefore associated with a higher operating frequency than arm 46A. By using two or more separate resonating element structures of different sizes, antenna resonating element 58 can be configured to cover a wider bandwidth or more than a single communications band of interest.
[0086] In certain embodiments of the present invention, the polymer composition may be particularly suitable for high-frequency antennas and antenna arrays used in base stations, repeaters (e.g., "femtocells"), relay stations, terminals, user equipment, and / or other suitable components of 5G systems. As used herein, "5G" generally refers to high-speed data communications via radio frequency signals. 5G networks and systems are capable of transmitting data at a faster rate than previous generations of data communication standards (e.g., "4G," "LTE"). As used herein, "5G frequency" may refer to a frequency of about 1.5 GHz or higher, about 2.0 GHz or higher in some embodiments, about 2.5 GHz or higher in some embodiments, about 3.0 GHz or higher in some embodiments, about 3 GHz to about 300 GHz in some embodiments, or higher, about 4 GHz to about 80 GHz in some embodiments, about 5 GHz to about 80 GHz in some embodiments, about 20 GHz to about 80 GHz in some embodiments, and about 28 GHz to about 60 GHz in some embodiments. Various standards and specifications have been published to quantify the requirements for 5G communications. For example, the International Telecommunications Union (ITU) released the International Mobile Telecommunications 2020 (IMT-2020) standard in 2015. The IMT-2020 standard specifies various data transmission standards for 5G (e.g., downlink and uplink data rates, latency, etc.). The IMT-2020 standard defines uplink and downlink peak data rates as the minimum data rates that a 5G system must support for uploading and downloading data. The IMT-2020 standard specifies a downlink peak data rate requirement of 20Gbit / s and an uplink peak data rate requirement of 10Gbit / s. As another example, the 3rd Generation Partnership Project (3GPP) recently released a new standard for 5G, called "5GNR". 3GPP released "Release 15" in 2018, which defined the "first phase" of 5G NR standardization. 3GPP defines 5G frequency bands as: Frequency Range 1 (FR1), which includes sub-6 GHz frequencies; and Frequency Range 2 (FR2), whose frequency bands are in the range of 20 GHz to 60 GHz. According to the standards published by 3GPP (e.g., Release 15 (2018)) and / or the IMT-2020 standard, the antenna system described in this article can meet or comply with the "5G" requirements.
[0087] In order to achieve high-speed data communication at high frequencies, antenna elements and arrays can use small feature sizes / spacing (e.g., fine pitch technology) that can improve antenna performance. For example, the feature size (spacing between antenna elements, width of antenna elements), etc., generally depends on the wavelength (λ) of the desired transmission and / or reception radio frequency propagated through the substrate dielectric on which the antenna elements are formed (e.g., nλ / 4, where n is an integer). In addition, beamforming and / or beam steering can be used to facilitate reception and transmission across multiple frequency ranges or channels (e.g., multiple-input multiple-output (MIMO), massive MIMO).
[0088] High frequency 5G antenna elements can have a variety of configurations. For example, the 5G antenna element can be or include a coplanar waveguide element, a patch array (e.g., a grid patch array), other suitable 5G antenna configurations. The antenna element can be configured to provide MIMO, massive MIMO functionality, beam steering, etc. As used herein, "massive" MIMO functionality generally refers to providing a large number of transmit and receive channels with an antenna array, such as 8 transmit (Tx) and 8 receive (Rx) channels (abbreviated as 8x8). Massive MIMO functionality can provide 8x8, 12x12, 16x16, 32x32, 64x64, or larger.
[0089] The antenna elements can have a variety of configurations and arrangements and can be manufactured using a variety of manufacturing techniques. As an example, the antenna elements and / or related elements (e.g., ground elements, feed lines, etc.) can use fine pitch technology. Fine pitch technology generally refers to the small spacing or fine spacing between their components or leads. For example, the characteristic size and / or spacing between antenna elements (or between antenna elements and ground planes) can be about 1,500 microns or less, in some embodiments 1,250 microns or less, in some embodiments 750 microns or less (e.g., center-to-center spacing of 1.5 mm or less), 650 microns or less, in some embodiments 550 microns or less, in some embodiments 450 microns or less, in some embodiments 350 microns or less, in some embodiments 250 microns or less, in some embodiments 150 microns or less, in some embodiments 100 microns or less, and in some embodiments 50 microns or less. However, it should be understood that smaller and / or larger characteristic sizes and / or spacings can be used within the scope of the present disclosure.
[0090] Due to this small feature size, the antenna system can be implemented with a large number of antenna elements in a small footprint. For example, the average antenna element density of the antenna array can be greater than 1000 antenna elements per square centimeter, in some embodiments greater than 2000 antenna elements per square centimeter, in some embodiments greater than 3000 antenna elements per square centimeter, in some embodiments greater than 4000 antenna elements per square centimeter, in some embodiments greater than 6000 antenna elements per square centimeter, and in some embodiments greater than about 8000 antenna elements per square centimeter. This compact arrangement of antenna elements can provide a greater number of channels for MIMO functionality per unit area of the antenna area. For example, the number of channels can correspond to (e.g., be equal to or proportional to) the number of antenna elements.
[0091] See also Figure 8 , shows an embodiment of a 5G antenna system 100, which also includes a base station 102, one or more relay stations 104, one or more user computing devices 106, one or more Wi-Fi repeaters 108 (e.g., "femtocells"), and / or other suitable antenna components for the 5G antenna system 100. The relay station 104 can be configured to facilitate communication between the user computing device 106 and / or other relay stations 104 and the base station 102 by relaying or "repeating" signals between the base station 102 and the user computing device 106 and / or the relay station 104. The base station 102 can include a MIMO antenna array 110, which is configured to receive and / or transmit radio frequency signals 112 using the relay station 104, the Wi-Fi repeater 108, and / or directly using the user computing device 106. The user computing device 106 is not necessarily limited by the present invention and includes devices such as 5G smartphones.
[0092] The MIMO antenna array 110 may employ beam steering to focus or direct the radio frequency signal 112 relative to the relay station 104. For example, the MIMO antenna array 110 may be configured to adjust an elevation angle 114 relative to the XY plane and / or a heading angle 116 defined in the ZY plane and relative to the Z direction. Similarly, one or more of the relay station 104, the user computing device 106, and the Wi-Fi repeater 108 may employ beam steering to improve reception and / or transmission capabilities relative to the MIMO antenna array 110 by directionally tuning the sensitivity and / or power transmission of the devices 104, 106, 108 relative to the MIMO antenna array 110 of the base station 102 (e.g., by adjusting one or both of the relative elevation angle and / or relative azimuth angle of each device).
[0093] Fig. 9A and 9B1 and 2 show a top view and a side view, respectively, of an example user computing device 106. The user computing device 106 may include one or more antenna elements 200, 202 (eg, arranged as a respective antenna array). Fig. 9A , the antenna elements 200, 202 may be configured to perform beam steering in the XY plane (as indicated by arrows 204, 206 and corresponding to relative azimuth angles). Fig. 9B , the antenna elements 200 , 202 may be configured to perform beam steering in the ZY plane (as indicated by arrows 204 , 206 ).
[0094] Fig.10 A simplified schematic diagram of multiple antenna arrays 302 connected using corresponding feed lines 304 (e.g., to a front-end module) is depicted. The antenna array 302 can be mounted to a side surface 306 of a substrate 308, which can be formed from a polymer composition of the present invention. The antenna array 302 can include multiple vertically connected elements (e.g., as a grid array). Therefore, the antenna array 302 can generally extend parallel to the side surface 306 of the substrate 308. Shielding can be optionally provided on the side surface 306 of the substrate 308 so that the antenna array 302 is located outside the shielding relative to the substrate 308. The vertical spacing distances between the vertically connected elements of the antenna array 302 can correspond to the "characteristic size" of the antenna array 302. Therefore, in some embodiments, these spacing distances can be relatively small (e.g., less than about 750 microns), so that the antenna array 302 is a "close pitch" antenna array 302.
[0095] Fig.11 A side view of a coplanar waveguide antenna 400 configuration is illustrated. One or more coplanar ground layers 402 may be arranged in parallel with an antenna element 404 (e.g., a patch antenna element). Another ground layer 406 may be separated from the antenna element by a substrate 408, which may be formed from a polymer composition of the present invention. One or more additional antenna elements 410 may be separated from the antenna element 404 by a second layer or substrate 412, which may also be formed from a polymer composition of the present invention. Dimensions "G" and "W" may correspond to "characteristic dimensions" of the antenna 400. The "G" dimension may correspond to the distance between the antenna element 404 and the coplanar ground layer 406. The "W" dimension may correspond to the width (e.g., line width) of the antenna element 404. Therefore, in some embodiments, dimensions "G" and "W" may be relatively small (e.g., less than about 750 microns), such that the antenna 400 is a "close pitch" antenna 400.
[0096] Fig. 12AAn antenna array 500 according to another aspect of the present disclosure is illustrated. The antenna array 500 may include a substrate 510 that may be formed from a polymer composition of the present invention and a plurality of antenna elements 520 formed thereon. The dimensions of the plurality of antenna elements 520 in the X direction and / or the Y direction may be approximately equal (e.g., square or rectangular). The plurality of antenna elements 520 may be approximately equally spaced in the X direction and / or the Y direction. The dimensions of the antenna elements 520 and / or the spacing therebetween may correspond to the "characteristic dimensions" of the antenna array 500. Therefore, in some embodiments, the dimensions and / or spacing may be relatively small (e.g., less than about 750 microns) such that the antenna array 500 is a "close pitch" antenna array 500. As indicated by the ellipsis 522, the number of columns of the antenna elements 520 shown in FIG. 12 is provided only as an example. Similarly, the number of rows of the antenna elements 520 is provided only as an example.
[0097] The tuned antenna array 500 may be used to provide massive MIMO functionality, such as in a base station (e.g., as described above with respect to Figure 8 More specifically, the RF interactions between the various elements can be controlled or tuned to provide multiple transmit and / or receive channels. Transmit power and / or receive sensitivity can be directionally controlled to focus or direct the RF signal, for example, Figure 8 The RF signal 112 is described. The tuned antenna array 500 can provide a large number of antenna elements 522 in a small footprint. For example, the average antenna element density of the tuned antenna 500 can be 1000 antenna elements per square centimeter or more. This compact arrangement of antenna elements can provide a greater number of channels for MIMO functionality per unit area. For example, the number of channels can correspond to (e.g., be equal to or proportional to) the number of antenna elements.
[0098] Fig. 12B An antenna array 540 formed by laser direct structuring is shown, which can be optionally used to form antenna elements. The antenna array 540 may include a plurality of antenna elements 542 and a plurality of feed lines 544 that connect the antenna elements 542 (e.g., to other antenna elements 542, front-end modules, or other suitable components). The antenna elements 542 may have respective widths "w" and spacing distances "S1" and "S2" therebetween (e.g., in the X and Y directions, respectively). These dimensions may be selected to enable 5G radio frequency communications at the desired 5G frequencies. More specifically, the dimensions may be selected to tune the antenna array 540 to transmit and / or receive data using radio frequency signals within the 5G spectrum. The dimensions may be selected based on the material properties of the substrate. For example, one or more of "w", "S1", or "S2" may correspond to a multiple (e.g., nλ / 4, where n is an integer) of a propagation wavelength ("λ") of a desired frequency through the substrate material.
[0099] As an example, λ can be calculated as follows:
[0100]
[0101] where c is the speed of light in vacuum, ∈ R is the dielectric constant of the substrate (or surrounding material), and f is the desired frequency.
[0102] Fig. 12C An example antenna configuration 560 is shown in accordance with aspects of the present disclosure. Antenna configuration 560 may include a plurality of antenna elements 562 arranged in parallel long edges of a substrate 564, which may be formed from a polymer composition of the present invention. Individual antenna elements 562 may have respective lengths "L" (and spacing distances therebetween) that tune antenna configuration 560 to receive and / or transmit at a desired frequency and / or frequency range. More specifically, such dimensions may be selected based on a propagation wavelength λ of the substrate material at a desired frequency, such as described above with reference to FIG. Fig. 12B as described.
[0103] Figures 13A to 13C Depicts a simplified sequential diagram of a laser direct structuring manufacturing process that can be used to form antenna elements and / or arrays according to the methods of the present disclosure. Fig.13A , the substrate 600 can be formed from the polymer composition of the present invention using any desired technique (e.g., injection molding). Fig. 13B As shown, laser 602 can be used to activate laser-activatable additives to form a circuit pattern 604 that may include one or more antenna elements and / or arrays. For example, the laser can melt conductive particles in a polymer composition to form the circuit pattern 604. Fig. 13C , the substrate 600 may be immersed in an electroless copper plating bath to plate the circuit pattern 604 and form antenna elements, element arrays, other components and / or conductors therebetween.
[0104] The present invention may be better understood with reference to the following examples.
[0105] Test Method
[0106] Melt viscosity: can be measured according to ISO test number 11443:2005 at 400s -1 Melt viscosity (Pa-s) was measured using a Dynisco LCR7001 capillary rheometer at a shear rate of 1000 rpm and a temperature 15°C above the melt temperature (e.g., about 350°C). The rheometer orifice (die) had a diameter of 1 mm, a length of 20 mm, an L / D ratio of 20.1, and an incident angle of 180°. The diameter of the barrel was 9.55 mm+0.005 mm, and the length of the rod was 233.4 mm.
[0107] Melting temperature: The melting temperature (Tm) can be determined by differential scanning calorimetry (DSC) as known in the art. The melting temperature is the differential scanning calorimetry (DSC) peak melting temperature as determined by ISO test number 11357-2:2013. Under the DSC procedure, as described in ISO standard 10350, the sample is heated and cooled at 20°C per minute using DSC measurements performed on a TA Q2000 instrument.
[0108] Deflection Temperature Under Load (DTUL): Deflection Temperature Under Load can be determined according to ISO Test No. 75-2:2013 (technically equivalent to ASTM D648-07). More specifically, a three-point bend test along the edge can be performed on a test strip sample having a length of 80 mm, a thickness of 10 mm, and a width of 4 mm, with a specified load (maximum external fiber stress) of 1.8 MPa. The specimen can be placed in a silicone oil bath, where the temperature is increased at 2°C per minute until it deflects 0.25 mm (0.32 mm for ISO Test No. 75-2:2013).
[0109] Tensile modulus, tensile stress, and tensile elongation: Tensile properties can be tested according to ISO test number 527:2012 (technically equivalent to ASTM D638-14). Modulus and strength measurements can be made on the same test strip sample with a length of 80 mm, a thickness of 10 mm, and a width of 4 mm. The test temperature can be about 23°C, and the test speed can be 1 mm / min or 5 mm / min.
[0110] Flexural modulus, flexural stress, and flexural elongation: Flexural properties may be tested according to ISO test number 178:2010 (technically equivalent to ASTM D790-10). The test may be performed over a 64 mm support span. The test may be performed on the center portion of an uncut ISO 3167 multipurpose bar. The test temperature may be about 23° C. and the test speed may be 2 mm / min.
[0111] Unnotched and Notched Charpy Impact Strength: Charpy properties can be tested according to ISO test number ISO 179-1:2010 (technically equivalent to ASTM D256-10, Method B). The test can be performed using Type 1 specimen dimensions (length 80 mm, width 10 mm and thickness 4 mm). When testing notched impact strength, the notch can be a Type A notch (0.25 mm base radius). The specimens can be cut from the center of a multi-purpose bar using a single tooth milling machine. The test temperature can be 23°C.
[0112] Dielectric constant (Dk) and dissipation factor (Df): The dielectric constant (or relative electrostatic permittivity) and dissipation factor are determined using a split-pillar dielectric resonator technique, such as described in Baker-Jarvis, et al., IEEE Trans. on Dielectric and Electrical Insulation, 5(4), p.571 (1998) and Krupka, et al., Proc. 7th International Conference on Dielectric Materials: Measurements and Applications, IEEE Conference Publication No. 430 (Sept. 1996). More specifically, a plate sample measuring 80 mm × 80 mm × 1 mm is inserted between two fixed dielectric resonators. The resonator measures the permittivity component in the plane of the specimen. Five samples are tested and the average value is recorded. Split-pillar resonators can be used for dielectric measurements in the low gigahertz region, such as 1 GHz to 2 GHz.
[0113] Thermal Cycle Test: The specimen is placed in a temperature controlled chamber and heated / cooled in a temperature range of -30°C to 100°C. Initially, the specimen is heated to 100°C and then immediately cooled. When the temperature reaches -30°C, the specimen is immediately heated again until it reaches 100°C. 23 heating / cooling cycles can be performed within a 3-hour period.
[0114] Example 1
[0115] Samples 1 to 7 are formed from various combinations of liquid crystal polymers (LCP 1 and LCP 2), copper chromite filler (CuCr2O4), glass fiber, alumina trihydrate (ATH), lubricant (polyethylene wax) and polytetrafluoroethylene (PTFE 1 and PTFE 2). LCP 1 is formed from 43% HBA, 20% NDA, 9% TA and 28% HQ. LCP 2 is formed from 60% HBA, 4% HNA, 18% TA and 18% BP. PTFE 1 is a polytetrafluoroethylene particle powder with a D50 particle size of 4μm, and PTFE 2 is a polytetrafluoroethylene particle powder with a D50 particle size of 40μm. Compounding was performed using an 18mm single screw extruder. The components are injection molded into plates (60mm×60mm) by the samples.
[0116] Table 1
[0117] 1 2 3 4 5 6 7 LCP 1 77.6 78 80 73 68 73 68 LCP 2 17.6 - - - - - - Fiberglass 15 15 13 15 15 15 15 Alumina trihydrate 0.2 0.2 0.2 0.2 0.2 0.2 0.2 Lubricants 0.2 0.2 0.2 0.2 0.2 0.2 0.2 Copper chromite 4.4 6.6 6.6 6.6 6.6 6.6 6.6 PTFE 1 - - - 5 10 - - PTFE 2 - - - - - 5 10
[0118] The thermal and mechanical properties of samples 1 to 7 were tested. The results are shown in Table 2 below.
[0119] Table 2
[0120]
[0121] Example 2
[0122] Sample 8 is formed from liquid crystal polymers (LCP 2 and LCP 3), hollow glass spheres, glass powder, glass fibers, and alumina trihydrate. LCP 3 is formed from 48% HNA, 2% HBA, 25% BP, and 25% TA. The glass powder has a dielectric constant of 4.8 as measured at a frequency of 1 GHz. Compounding was performed using a 25 mm single screw extruder.
[0123] Table 3
[0124] sample 8 LCP 3 49.8 LCP 2 15.4 Hollow glass ball 17.0 Glass powder 1.0 Glass fiber (4mm long) 10.0 Alumina trihydrate 0.2 Copper chromite 6.6
[0125] The thermal and mechanical properties of the samples were tested. The results are shown in Table 4 below.
[0126] Table 4
[0127] sample 8 Dielectric constant (2GHz) 3.07 Dissipation Factor (2GHz) 0.0043 Dielectric constant (10GHz) 3.14 Dissipation Factor (10GHz) 0.0035 <![CDATA[1000s -1 Melt viscosity at (Pa-s)]]> 55.5 <![CDATA[400s -1 Melt viscosity at (Pa-s)]]> 88.9 Melting temperature(℃) 338.6 DTUL at 1.8MPa(℃) 217 Tensile strength(MPa) 81 Tensile modulus (MPa) 7,658 Tensile elongation (%) 1.41 Bending strength(MPa) 116 Flexural modulus (MPa) 7,241 Bending elongation (%) 1.91 <![CDATA[Charpy notched impact strength (kJ / m 2 )]]> 3.1 <![CDATA[Charpy unnotched impact strength (kJ / m 2 )]]> 7.3
[0128] Without departing from the spirit and scope of the present invention, those of ordinary skill in the art may make these and other modifications and variations to the present invention. In addition, it should be understood that the aspects of the various embodiments may be interchangeable as a whole or in part. In addition, those of ordinary skill in the art will appreciate that the foregoing description is exemplary only and is not intended to limit the present invention as further described in the appended claims.
Claims
1. A laser-activatable polymer composition comprising: at least one laser-activatable additive and at least one high naphthalene thermotropic liquid crystal polymer, wherein the high naphthalene thermotropic liquid crystal polymer contains repeating units derived from naphthalene hydroxycarboxylic acid and / or naphthalene dicarboxylic acid in an amount of 10 mol.% or more, wherein the polymer composition exhibits a dielectric constant of 4 or less and a dissipation factor of 0.01 or less measured at a frequency of 2 GHz, wherein the composition has a melt viscosity of 55.5 Pa-s or less, wherein the melt viscosity is measured at 1000 seconds according to ISO Test No. 11443:2005 -1 The shear rate is measured at a temperature of 15°C above the melting temperature of the composition.
2. The polymer composition according to claim 1, wherein The polymer composition has a melting temperature of 200°C to 400°C.
3. The polymer composition according to claim 1 or 2, wherein The liquid crystal polymer constitutes 40 wt. % to 99 wt. % of the polymer composition.
4. The polymer composition according to claim 1, wherein The high naphthalene thermotropic liquid crystal polymer comprises repeating units derived from one or more aromatic dicarboxylic acids, one or more aromatic hydroxycarboxylic acids, or a combination thereof.
5. The polymer composition according to claim 4, wherein The aromatic hydroxycarboxylic acid includes 4-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid or a combination thereof.
6. The polymer composition according to claim 4, wherein The aromatic hydroxycarboxylic acid includes terephthalic acid, isophthalic acid, 2,6-naphthalene dicarboxylic acid or a combination thereof.
7. The polymer composition according to claim 4, wherein The high naphthalene thermotropic liquid crystal polymer further comprises repeating units derived from one or more aromatic diols.
8. The polymer composition according to claim 7, wherein The aromatic diol includes hydroquinone, 4,4'-biphenol or a combination thereof.
9. The polymer composition according to claim 1, wherein The high naphthalene thermotropic liquid crystal polymer is fully aromatic.
10. The polymer composition according to claim 1, wherein The high naphthalene thermotropic liquid crystal polymer includes a repeating unit derived from 2,6-naphthalene dicarboxylic acid in an amount of 10 mol. % or more.
11. The polymer composition according to claim 1, wherein The liquid crystal polymer includes a repeating unit derived from 6-hydroxy-2-naphthoic acid in an amount of 30 mol. % or more.
12. The polymer composition according to claim 10, wherein The liquid crystal polymer includes a repeating unit derived from 6-hydroxy-2-naphthoic acid in an amount of 50 mol. % or more.
13. The polymer composition according to claim 10, wherein The liquid crystal polymer includes a repeating unit derived from 6-hydroxy-2-naphthoic acid in an amount of 70 mol. % or more.
14. The polymer composition according to claim 10, wherein The liquid crystal polymer includes repeating units derived from 6-hydroxy-2-naphthoic acid and 4-hydroxybenzoic acid in a molar ratio of 0.1 to 40.
15. The polymer composition according to claim 10, wherein The liquid crystal polymer includes repeating units derived from 6-hydroxy-2-naphthoic acid and 4-hydroxybenzoic acid in a molar ratio of 1 to 5.
16. The polymer composition according to claim 1, wherein The high naphthalene thermotropic liquid crystal polymer exhibits a water absorption rate of 0.015% or less after immersion in water for 24 hours according to ISO 62-1:2008.
17. The polymer composition according to claim 1, wherein The high naphthalene thermotropic liquid crystal polymer exhibits a moisture absorption rate of 0.01% or less after exposure to a relative humidity of 50% at a temperature of 23°C according to ISO 62-4:2008.
18. The polymer composition according to claim 1, wherein The laser-activatable additive comprises spinel crystals having the following general formula: AB2O4 in, A is a divalent metal cation; and B is a trivalent metal cation.
19. The polymer composition according to claim 18, wherein The spinel crystals include MgAl2O4, ZnAl2O4, FeAl2O4, CuFe2O4, CuCr2O4, MnFe2O4, NiFe2O4, TiFe2O4, FeCr2O4, MgCr2O4 or a combination thereof.
20. The polymer composition according to claim 1, wherein The polymer composition is free of dielectric materials.
21. The polymer composition of claim 1 further comprising at least one fibrous filler.
22. The polymer composition according to claim 21, wherein The fibrous filler includes glass fibers.
23. The polymer composition according to claim 21, wherein The fibrous filler has an aspect ratio of 2 or more.
24. The polymer composition according to claim 21, wherein The weight ratio of the fibrous filler to the laser-activatable additive is 1 to 5.
25. The polymer composition according to claim 1, wherein The polymer composition also comprises a particulate filler.
26. The polymer composition according to claim 25, wherein The particulate filler includes mica.
27. The polymer composition of claim 1, wherein The polymer composition exhibits a dielectric constant of 1.5 to 4 at a frequency of 2 GHz.
28. The polymer composition of claim 1, wherein: The polymer composition exhibits a dissipation factor of 0.0009 or less at a frequency of 2 GHz.
29. The polymer composition according to claim 1, wherein In the 1,000s -1 The composition has a melt viscosity of 5 to 37 Pa-s measured at a shear rate of 1000 Å and a temperature of 350° C.
30. The polymer composition of claim 1, wherein: The composition comprises 40 wt.% to 99 wt.% of a thermotropic liquid crystal polymer, 0.1 wt.% to 20 wt.% of a laser-activatable additive, and 1 wt.% to 40 wt.% of a fiber filler.
31. The polymer composition according to claim 1, further comprising at least one low-naphthalene thermotropic liquid crystal polymer containing repeating units derived from naphthalenehydroxycarboxylic acid and / or naphthalene dicarboxylic acid in an amount of less than 10 mol%.
32. The polymer composition according to claim 31, wherein The low naphthalene thermotropic liquid crystal polymer constitutes 0.5 wt. % to 45 wt. % of the polymer composition, and the high naphthalene thermotropic liquid crystal polymer constitutes 55 wt. % to 99.5 wt. % of the polymer composition.
33. The polymer composition of claim 1, wherein: The composition comprises a hydrophobic material.
34. The polymer composition according to claim 33, wherein The hydrophobic material includes polytetrafluoroethylene.
35. The polymer composition of claim 1, wherein: The composition comprises a hollow filler.
36. A moulded part comprising the polymer composition of any preceding claim.
37. A molded part according to claim 36, wherein: One or more conductive elements are formed on a surface of the component.
38. An antenna system comprising a substrate comprising the polymer composition of any one of the preceding claims and at least one antenna element configured to transmit and receive radio frequency signals, wherein the antenna element is coupled to the substrate.
39. The antenna system of claim 38, wherein: The radio frequency signal is a 5G signal.
40. The antenna system of claim 38, wherein: The antenna elements have a characteristic dimension of less than 1,500 microns.
41. The antenna system of claim 38, wherein: The at least one antenna element includes a plurality of antenna elements.
42. The antenna system of claim 41, wherein: The plurality of antenna elements are spaced apart at a spacing distance of less than 1,500 microns.
43. The antenna system of claim 41, wherein: The plurality of antenna elements includes at least 16 antenna elements.
44. The antenna system of claim 41, wherein: The plurality of antenna elements are arranged in an array.
45. The antenna system of claim 44, wherein: The array is configured for at least 8 transmit channels and at least 8 receive channels.
46. The antenna system of claim 44, wherein: The array has an average antenna element density of greater than 1,000 antenna elements per square centimeter.
47. The antenna system of claim 38, further comprising a base station, and wherein: The base station comprises the at least one antenna element.
48. The antenna system of claim 38, further comprising at least one of a user computing device or a repeater, and wherein: At least one of the user computing device or the base repeater station includes the at least one antenna element.
Citation Information
Patent Citations
High strength thermotropic liquid crystalline polymer
CN105358657A
Liquid Crystalline Polymer Composition for Melt-Extruded Substrates
US20140142571A1